New insights into the association between cardiometabolic index with metabolic profile, nutritional status, and inflammaging in older adults - Ramuth, Sylvia; Carvalho, Rafael Leite; Moscogliato, Rafael Zappitelli; Rossi, Marcelo; Nali, Luiz Henrique da Silva; Colombo-Souza, Patrícia; Do Amaral, Jônatas Bussador; Furtado, Guilherme Eustáquio; Brito, Tábatta Renata Pereira de; Bachi, André Luis Lacerda (Frontiers in Aging, 2026)
IntroductionCardiometabolic index (CMI) has been highlighted as a useful tool for predicting cardiovascular and metabolic disease, but its association with systemic inflammatory status in the aged population is not yet fully understood. Thus, we investigated the association between the CMI and the triad -metabolic profile X body mass index X inflammaging -in older adults classified as having or not having obesity.MethodsA total of 132 older adults of both sexes (women-68; men-64, mean age of 71.3±6.5 years), participated in this study. Demographic and anthropometric data, as well as blood samples, were collected to assess blood glucose, lipids, protein, and inflammatory profiles.ResultsInitially, the volunteers were separated according to the CMI values into two groups: G1 (<50% of the mean CMI value) and G2 (>50% of the mean CMI value). Volunteers in the G2 group, regardless of gender, presented not only lower HDL-c values but also higher weight, BMI, levels of total cholesterol, LDL-c, triglycerides, and the triglycerides to HDL ratio (TG/HDL) than the G1 group. The correlation analysis and linear multivariate regression, with CMI-adjustment, showed a significant positive association with BMI, as well as with pro-inflammatory cytokines, both in the G1 and G2 groups, regardless of gender. After that, the volunteers were separated according to BMI into normal weight and those with obesity. In general, the G2 subgroups with obesity showed higher levels of pro-inflammatory cytokines IL-1β, IL-6, IFN-γ, and TNF-α than the respective G1 subgroups, and also an association of CMI in favor of a pro-inflammatory systemic status, particularly in the older women group.ConclusionIn this cross-sectional study, our findings not only reinforce the potential role of CMI in cardiovascular risk assessment but also may putatively suggest that this index has an interesting association with systemic pro-inflammatory status in older adults, preferentially with obesity.